2019
DOI: 10.1111/ijfs.14145
|View full text |Cite
|
Sign up to set email alerts
|

Generation of bioactive prolyl‐hydroxyproline (Pro‐Hyp) by oral administration of collagen hydrolysate and degradation of endogenous collagen

Abstract: Summary Hydroxyproline‐containing di‐ and tripeptides increase in human blood plasma after ingestion of collagen hydrolysate in a dose‐dependent manner. Prolyl‐hydroxyproline (Pro‐Hyp) and hydroxyprolyl‐glycine (Pro‐Gly) are the main food‐derived collagen peptides present in human blood plasma. Pro‐Hyp increases the number of fibroblasts migrating from the mouse skin and enhances the growth of fibroblasts attached to the collagen gel. Pro‐Hyp is also generated from endogenous collagen in the granulation tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Therefore, we concluded that grafted cells could not directly participate in granulation tissue formation, but some components in the tissue suspension solution stimulate the development of granulation tissue. The extracellular components in the solution may contain cytokines [ 26 ], growth factors [ 6 , 27 , 28 ], proteinases [ 29 ] and matrix components [ 30 ], which include tumor necrotic factor, interleukins-1 and 6, transforming growth factor (TGF)-β, vascular endothelial growth factor, FGF, platelet-derived growth factor, epidermal growth factor, hepatocyte growth factor and matrix metalloproteinases, as well as collagens and collagen-derived proline-hydroxyproline peptides [ 31 , 32 ]. All of these factors are candidates of paracrine factors for wound-healing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we concluded that grafted cells could not directly participate in granulation tissue formation, but some components in the tissue suspension solution stimulate the development of granulation tissue. The extracellular components in the solution may contain cytokines [ 26 ], growth factors [ 6 , 27 , 28 ], proteinases [ 29 ] and matrix components [ 30 ], which include tumor necrotic factor, interleukins-1 and 6, transforming growth factor (TGF)-β, vascular endothelial growth factor, FGF, platelet-derived growth factor, epidermal growth factor, hepatocyte growth factor and matrix metalloproteinases, as well as collagens and collagen-derived proline-hydroxyproline peptides [ 31 , 32 ]. All of these factors are candidates of paracrine factors for wound-healing.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute bioavailability of collagen hydrolysates to the small intestine and extra-intestinal tissues in various amino acid and peptide forms is about 90-95% in humans and animals, depending on species and age. In humans, ingestion of collagen hydrolysates increases the concentrations of at least 11 Hyp-containing peptides (Pro-Hyp, Hyp-Gly, Ala-Hyp, Ile-Hyp, Leu-Hyp, Phe-Hyp, Glu-Hyp, Pro-Hyp-Gly, Gly-Pro-Hyp, Ala-Hyp-Gly, and Ser-Hyp-Gly) in plasma (Sato et al 2019). A majority of studies have shown that Pro-Hyp and Hyp-Gly, which are resistant to peptidases in the human plasma, are the most (about 50%) and second most abundant food-derived 4-hydroxyproline-containing peptides in the plasma of healthy adult humans, rats and mice after consuming collagen hydrolysates (Osawa et al 2018;Sato et al 2019;Shigemura et al 2014).…”
Section: Absorption Of 4-hydroxyproline By the Small Intestine And Trmentioning
confidence: 99%
“…Pro-Hyp, Leu-Hyp, and Gly-Pro-Hyp were significantly increased in the mouse ear with dermatitis, whereas these peptides did not increase in other ear without dermatitis in the same animal (Kusubata et al, 2015 ; Sato et al, 2019 ). Among these, Pro-Hyp was the most abundant; however, isotope-labeled Pro-Hyp was specifically cleaved in the ear with dermatitis.…”
Section: Generation Of Collagen-derived Di-peptides In Tissuesmentioning
confidence: 97%